Acute arsenic exposure induces inflammatory responses and CD4+ T cell subpopulations differentiation in spleen and thymus with the involvement of MAPK, NF-kB, and Nrf2. (January 2017) - Duan, Xiaoxu; Gao, Shuang; Li, Jinlong; Wu, Liuzhong; Zhang, Yang; Li, Wei; Zhao, Lu; Chen, Jinli; Yang, Shan; Sun, Guifan; Li, Bing
Highlights: Arsenic induced inflammatory responses in immune organs. Arsenic affected CD4 + T cells differentiation in immune organs. Arsenic mediated oxidative injuries in immune organs. Arsenic activated MAPK, NF-kB and Nrf2 pathway in immune organs. Abstract: Increasing lines of evidence indicate that arsenic may be associated with immune related problems, but its detailed effects on immune organs are poorly understood. The objective of this study was to explore inflammatory responses and T cell differentiation of arsenic exposure in spleen and thymus. Female C57BL/6 mice were used as a model to systemically administration 2.5, 5 and 10 mg/kg NaAsO2 intra-gastrically for 24 h. We found that arsenic significantly decreased the spleen and thymus weights and indices, and flow cytometry revealed that arsenic decreased the relative frequency of CD4 + T cell subpopulation and the ratios of CD4/CD8 in spleen. In contrast, serum concentration of tumor necrosis factor α (TNF-α), IL-1β and IL-6 as well as the mRNA of key inflammatory mediators in spleen and thymus, including transforming growth factor β ( Tgf-β), Tnf-α, Il-12, Il-1β and Il-6 were significantly increased in arsenic-treated mice compared to the control as assayed by ELISA and real time PCR, respectively. In addition, arsenic increased the expression of T helper cell 1 (Th1), Th2 and regulatory T cell (Treg) −associated transcription factors and cytokines as well as decreased Th17-associated transcription factors and cytokines. Moreover, arsenic enhanced oxidative stress and induced the activation of extracellular-signal-regulated kinases 1/2 (ERK1/2), c-Jun N-terminal kinases (JNK) and p38 and their downstream transcription factors nuclear factor kappa B (NF-kB) and nuclear factor E2-related factor 2 (Nrf2), which comprise important mechanistic pathways involved in immune-inflammatory manifestations. Together, these results provide a novel strategy to block the arsenic-dependent impairments in immune responses.